Designing a wind farm for individual energy consumers - Egamov D; Azamatov Abdumutallib Ulugbek o’g’li; Raxmatullayev Shamsiddin Hakimboy õğli (Лучшие интеллектуальные исследования, 2024)
ABSTRACT an Wind resource assessment can assess wind energy potential globally, by country or region, or for a specific area. The potential of wind resources in our region has been studied in detail, precautions and possibilities of wind power plants that produce electricity from low-speed wind have been studied. Current wind power plants that work even at low wind speeds have been analyzed and comments on their achievements and existing shortcomings have been made. Also, the article recommends some projects on the design of wind power devices operating at low wind speed. The characteristics of devices operating at low wind speed were studied through the conducted experiment.